Sudden infant death syndrome (SIDS) - How to reduce the risk? - Dengler, Barbara; Wolanin, Marta; Stawikowski, Cezary; Zielonka, Bartłomiej; Osińska, Aleksandra; Wolanin, Izabela; Madej, Karolina; Stachyra, Bartłomiej; Kowalczyk, Ilona; Krasa, Aleksandra (Journal of Education, Health and Sport, 2023)
Sudden infant death syndrome (SIDS) is a complex, multifactorial phenomenon with an etiology that has not been fully clarified to this day. Despite a noticeable decrease in the number of SIDS cases worldwide, sudden infant death syndrome remains one of the most common causes of death among children in infancy. Sudden infant death syndrome is still the subject of scientific research aimed to clearly determine and identify potential pathogenetic factors responsible for the occurrence of SIDS. Many years of efforts to clarify the etiology of the discussed issue have made it possible to characterize important factors that increase the risk of sudden infant death syndrome. In addition, research has made it possible to develop important approaches that make a significant contribution to reduce the risk of SIDS in an infant. Complete knowledge of the specific conditions that have a protective effect against SIDS will significantly reduce the risk of sudden infant death syndrome, so a very important aspect is not only their precise analysis, but also their propagation among the public.